FORMS, METHODS AND TOOLS USED IN THE FORMATION OF PERSONAL QUALITIES IN CHILDREN (Multidisciplinary Journal of Science and Technology, 2026)
This article analyzes forms, methods, and tools that educators and caregivers use to support the formation of personal qualities in children, including responsibility, empathy, self control, perseverance, honesty, respect, and civic mindedness. The central idea is that personal qualities are not taught as isolated slogans but are developed through repeated experiences in relationships, routines, and meaningful tasks. The paper clarifies how moral development, social and emotional learning, and character education intersect in everyday schooling and family life. It describes practical forms of work, such as classroom meetings, project based learning, cooperative tasks, service learning, clubs, mentoring, and family partnership events. It then explains core methods, including adult modeling, guided practice, discussion, storytelling, role play, reflection, positive reinforcement, restorative dialogue, and structured feedback. The article also reviews tools that make these approaches concrete, such as journals, portfolios, behavior agreements, rubrics for collaboration and self management, literature and film fragments for ethical discussion, games, art activities, peer mediation scripts, and digital resources used with clear boundaries. Special attention is given to age appropriateness, inclusion, cultural sensitivity, and safety, because poorly designed character work can become moralizing, unfair, or even harmful. The conclusion proposes a coherent framework: create a supportive environment, teach specific skills, provide practice in real tasks, and assess growth through observable behavior and reflection, not through labels.